VD_FINDINFO 4/2011/PBH vom 21. Januar 2011 - VD Tribunal cantonal (2011)
MESURE PROVISIONNELLE, SÛRETÉS, ACTION EN PÉTITION D'HÉRÉDITÉ | 598 al. 2 CC, 598 CC, 101 CPC, 109 al. 1 CPC, 17 CPC, 91 let. a CPC, 91 let. c CPC, 92 al. 1 CPC, 18 al. 1 LFors, 18 LFors, 33 LFors, 404 CPC (CH)